Aesthetic expression of Masjid Ubudiah Kuala Kangsar Series / Norhaslinda Shafie... [et al.] - Shafie, Norhaslinda; Azuddin, Muhammad Asri; Halili, Nur Akma; Azman, Muhammad Firdaus; Sulaiman, Mohamad Zaidi (UiTM Perak Press, 2022)
Nowadays, our environment exists with thousands of images and photographs.mImages and photographs are dominant to human communication and a variety of appearances. This artwork is to survey the power of the Tawhid concept in the photograph architecture of Masjid Ubudiah, Kuala Kangsar. Thus, this writing of artwork uses visual research analysis to identify the usual photography of Masjid Ubudiah and to insert the concept of Tawhid. Brings to the end, there are three principles, the modular structure, repetition, and dynamism been applied in the artwork of aesthetic expression of Masjid Ubudiah, Kuala Kangsar series.